Discursos míticos e figuras míticas: o uso dos mitos nas Eneádas de Plotino - Loraine de Fatima Oliveira (2008)
This thesis deals with the usage of the myths in Plotinus Enneads, dividing them into two great groups: discourses and mythological figures. The first group concerns to the genealogical myths, which provide an opportunity for embracing all the levels of the reality. The second group concerns to the myths which, not being disposed in the genealogicalstructure, function as images of some given aspect of the reality. As there is in the treatises of Plotinus a certain variety of functions and procedures, linked to the usage of the myth, it is tried, on the one hand, to define the specifity of the discourses and of the figures related to the discoursive manners of the text on the whole, and on the other hand in relation to the broader notion of image and a more specific notion of visual image. Thus is the thesis divided into three parts: the first part deals with the discourses on the whole and with the mythical discourses related to their genealogy. Specially is focused the problem of time in order todefine the specific sense of them. The second part analyses the genealogies of the treatises. The third part tries to define the notion of image regarding to the myths, starting from the lexical field of the myth, and analyses some mythical figures.